Evaluasi Usability Aplikasi Mobile Banking Dengan Menggunakan Usability Testing (Studi kasus: Aplikasi Jakone Mobile PT.Bank DKI) - Muhamad Wido Rahman; Widhy Hayuhardhika Nugraha Putra; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Jakone mobile is an internet banking service product owned by PT. Bank DKI. In its application, users need information on Jakone cell phones that do not require details so that users feel less confident when using. In addition, users can make complicated transactions on the Jakone mobile application because the application often corrects errors, making customers feel dissatisfied. Based on these problems this application needs to be evaluated for usability to measure the usefulness of the Jakone mobile application and find problems and be given recommendations to improve the Jakone mobile application in the future. This study uses usability testing methods with aspects of learning ability, effectiveness, and efficiency. The distribution of the SUS questionnaire was used to obtain aspects of satisfaction. Usability testing and interviews are conducted by 5 people using the new Jakone mobile application. The SUS questionnaire is conducted by 20 active users of the Jakone mobile application. Based on the evaluation results, the learning aspects were 94%, the effectiveness aspects of the evaluation were 11%, the efficiency aspects were 19%, and the satisfaction aspects were obtained 67% of the SUS questionnaire which showed the application needed improvement. Based on the results of the interview found problems with aspects of learnbility, namely descriptions not given, difficulty choosing icons, The satisfaction aspect is considered important, button is not consistent. The efficiency aspect that is considered important is a menu that is hard to find. From these considerations a discussion based on appropriate usability guidelines is provided from the debate.